New architectures for space power systems - Ehsani, M.; Bilgiç, Mehmet Oruç; Patton, Alton D.; Mitra, J. (IEEE, 1995)
Electric power generation and conditioning have experienced revolutionary development over the past two decades. Furthermore, new materials such as high energy magnets and high temperature superconductors are either available or on the horizon. Our work is based on the premise that new technologies are an important driver of new power system concepts and architectures. This observation is borne out by the historical evolution of power systems both in terrestrial and aerospace applications. This paper introduces new approaches to designing space power systems by using several new technologies. Two new architectures are introduced: the current source current intensive system and the articulate system. Basic characteristics of these systems have been investigated. Some aspects of the articulate system architecture, as discussed in this paper can be implemented in the short term. Flexible AC transmission systems which are now undergoing rapid development and implementation, can be regarded as a subset of the family of control methodologies which constitute the realm of articulate systems.
Keywords: space vehicle power plants; technological forecasting; superconducting magnet energy storage; space power systems; architectures; current source current intensive system; flexible AC transmission systems; articulate system; superconductive magnetic energy storage